GIFT CULTURE DI ERA DIGITAL: KAJIAN FIQH KONTEMPORER MELALUI PENDEKATAN TAJRIBI TERHADAP PRAKTIK HADIAH DALAM “MARAPTHON” STREAMER @YB - Lubis, Willy Akmansyah (Muẚṣarah: Jurnal Kajian Islam Kontemporer, 2025)
The phenomenon of gift-giving in the digital world, especially on streaming platforms and social media, has grown rapidly with the presence of various donation features and support for content creators. This practice raises questions about the legal and cultural aspects of gifts from an Islamic perspective, especially related to the teachings of fiqh which focus on the relationship between the giver, the recipient, and the benefits contained therein. This paper aims to examine integrative fiqh on digital gift practices, with a case study on the streamer @yb who uses the tajribi (experimental) approach to assess the social and economic impacts of this gift practice in the digital world. This study uses a qualitative approach with direct observation methods of phenomena on social media and analysis of content received by the streamer. The results of the study indicate that the gift practice in streaming @yb has significant social value, creates a relationship between content creators and their audiences, and can affect the personal economic aspects and digital communities and from a contemporary fiqh perspective, this donation practice is generally more inclined towards the tabarru' contract (voluntary grant) because it is given spontaneously without conditions and without any demands for a specific return.